Analisis keharusan pengembangan materi ajar BIPA 1 bagi pemelajar berbahasa pertama bahasa Prancis - Nadia Karima; Liliana Muliastuti; Sri Harini Ekowati (Badan Pengembangan dan Pembinaan Bahasa, 2023)
This research is based on the need for the development of BIPA 1 teaching materials which are not only good in terms of content but also effective for use by teachers and target students. In order to achieve this goal, research was conducted on Requirements Analysis which is part of the Needs Analysis for the development of BIPA 1 teaching materials for first-speaking French speakers. This research is a descriptive qualitative research with literature review method. From this study, the results were obtained in the form of a Requirements Analysis result table which contained a merger between the Elements of Functions table at Cadre Européen Commun de Références pour les Langues (CECRL) level A1 and the Pengetahuan yang Dikuasai table in Capaian Lulusan Khusus BIPA 1 and the table of Aspek Kebahasaan in Standar Kompetensi Lulusan BIPA 1 as stated in Permendikbud number 27 of 2017.